ANTICOAGULANTS AND CORTICOSTEROIDS IN COVID-19 – WHAT DO WE KNOW SO FAR? - Milenković, Marija; Dukić, Marija; Rović, Ivan; Šijan, Đuro; Hadžibegović, Adi; Popadić, Višeslav; Klašnja, Slobodan; Brajković, Milica; Zdravković, Marija (Srpski medicinski časopis Lekarske komore, 2022)
It has been a year and a half since the fight against the COVID-19 pandemic started. In today’s protocols for the treatment of COVID-19 and the prevention of its complications, corticosteroid therapy and anticoagulant therapy have a crucial part. The goal of this article is to show, based on available data, both the benefits and the disadvantages of corticosteroid and anticoagulant therapy in treating the infection caused by the Sars-CoV-2 virus. At the very onset of the pandemic, an increased frequency of thrombotic events negatively impacting the course and outcome of the disease, was registered. It has been observed that increased values of D-dimer in patients with COVID-19 do not correlate with the presence of venous thrombosis and are not reliable in the detection of deep vein thrombosis and pulmonary thromboembolism. According to the National Protocol for Treating COVID-19 (Version 12), anticoagulant therapy is recommended in hospitalized patients. Due to the risk of different side effects, such as bleeding and heparin-induced thrombocytopenia, a careful use of anticoagulant therapy is necessary, as well as close monitoring of its effects. With respect to corticosteroids, their efficacy in patients with moderate and severe clinical presentation of COVID-19, who are in need of oxygen support, was analyzed. Corticosteroids have proven efficient in decreasing mortality, decreasing the need for mechanical ventilation, decreasing the length of stay in intensive care units, as well as in shortening the length of hospital stay. Assessing the individual benefits and risks before introducing these drugs into the therapy of a patient with confirmed COVID-19 is of vital importance for achieving the desired effects of the therapy.